Atrophy of medial temporal lobes on MRI in "probable" Alzheimer's disease and normal ageing: diagnostic value and neuropsychological correlates. Issue 10 (October 1992) - Scheltens, P; Leys, D; Barkhof, F; Huglo, D; Weinstein, H C; Vermersch, P; Kuiper, M; Steinling, M; Wolters, E C; Valk, J
Abstract : Magnetic resonance imaging (MRI) has shown a great reduction in medial temporal lobe and hippocampal volume of patients with Alzheimer's disease as compared to controls. Quantitative volumetric measurements are not yet available for routine clinical use. We investigated whether visual assessment of medial temporal lobe atrophy (MTA) on plain MRI films could distinguish patients with Alzheimer's disease (n = 21) from age matched controls (n = 21). The degree of MTA was ascertained with a ranking procedure and validated by linear measurements of the medial temporal lobe including the hippocampal formation and surrounding spaces occupied by cerebrospinal fluid. Patients with Alzheimer's disease showed a significantly higher degree of subjectively assessed MTA than controls (p = 0.0005). Linear measurements correlated highly with subjective assessment of MTA and also showed significant differences between groups. Ventricular indices did not differ significantly between groups. In Alzheimer's disease patients the degree of MTA correlated significantly with scores on the mini-mental state examination and memory tests, but poorly with mental speed tests. This study shows that MTA may be assessed quickly and easily with plain MRI films. MTA shown on MRI strongly supports the clinical diagnosis of Alzheimer's disease, is related to memory function, and seems to occur earlier in the disease process than does generalised brain atrophy.